Representasi Patriotisme Pada Film Soegija (Analisis Semiotika John Fiske) - Nexen Alexandre Pinontoan (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2020)
This study aims to determine the representation of patriotism in the film Soegija. The research question posed is how the representation of patrotism in the film of Soegija. The method of this research is qualitative with John Fiske semiotics analysis. His research subject is Soegija film. Data collection was obtained through observation, using primary and secondary data collection techniques. The data obtained directly from the research object is the film Soegija. The results showed that the representation of Patriotism from the film Soegija by using the code reality, representation and ideology, through the scene of conversation, technical drawing and location of the filing. The film reveals that the characteristic of patriotism places the unity of the nation and the state above personal and group interests, namely Soegija who seeks ways to restore conditions to good condition, by carrying out orders to each region to form regional leaders to overcome the chaos that occurs. Soegija really has a religious code as the leader of the Catholic community, strong in defending the church where sanctified by the Catholic community. Soegija considers the people who suffer more and need food more than the leader. If the people are full let the last leaders feel full. And let it be if the people are hungry, the first leader feels hungry. Soegija felt as a good Catholic, should also be a good patriot and love each other. Soegija attaches importance to the common interests, especially the interests of the people, so that they can live better. The conclusion of the research is The Films